2011
DOI: 10.1038/cdd.2011.127
|View full text |Cite|
|
Sign up to set email alerts
|

MiR-181 mediates cell differentiation by interrupting the Lin28 and let-7 feedback circuit

Abstract: MicroRNAs (miRNAs) have attracted attention because of their key regulatory functions in many biological events, including differentiation and tumorigenesis. Recent studies have reported the existence of a reciprocal regulatory loop between the family of let-7 miRNAs and an RNA-binding protein, Lin28, both of which have been documented for their important roles during cell differentiation. Hence, using bipotent K562 human leukemia cells and human CD34 þ hematopoietic progenitor cells as research models, we dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
106
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(111 citation statements)
references
References 39 publications
(13 reference statements)
2
106
0
Order By: Relevance
“…However, we found that protein levels of SHP2 were not changed in HepG2 cells or the liver of mice when miR-181a was overexpressed (data not shown). RNA-binding protein LIN-28 homologue A, another target of miR-181a, has also been reported as a positive regulator of insulin signalling [46,47]. Foxo1 and Pgc1α were also predicted as miR-181a targets by PicTar or TargetScan.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that protein levels of SHP2 were not changed in HepG2 cells or the liver of mice when miR-181a was overexpressed (data not shown). RNA-binding protein LIN-28 homologue A, another target of miR-181a, has also been reported as a positive regulator of insulin signalling [46,47]. Foxo1 and Pgc1α were also predicted as miR-181a targets by PicTar or TargetScan.…”
Section: Discussionmentioning
confidence: 99%
“…7 To date, about 1800 human miRNAs have been identified (miRBase Release 21.0, http://www.mirbase.org/), 8 including many that participate in key cellular processes, such as apoptosis, proliferation, and differentiation. 9 MiRNA misexpressions or mutations result in a gain or loss of miRNA function, resulting in the down-or up-regulation of the target protein. More importantly, the successful use of antagomirs to silence miRNAs in mice 10 and nonhuman primates 11 suggests the possible therapeutic use of miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…The mammalian genome encodes two homologues of the C. elegans lin-28 genes (LIN28A and LIN28B) (3,4), which may control gene expression by distinct molecular mechanisms (5). They are important in processes such as embryogenesis (6), skeletal myogenesis (7), germ cell development (8,9), neurogliogenesis (10,11), differentiation (12,13), lymphopoiesis (14), and glucose metabolism (15). Genome-wide association studies have implicated the LIN28B locus in controlling both height and the timing of menarche in humans (16 -20).…”
mentioning
confidence: 99%